The Impact of Humor Styles on Attachment and Conflict Management of Young Adults - Gupta, Jahnavi (My University, 2023)
Personal differences in Humour styles have been determined. A sense of humour is a significant psychological personality trait, it affects how well people manage conflicts and plays a role in social relationships, involving adult attachments. The study aimed at studying the effect of humour style on young adults' attachment and conflict management. An online survey was completed by 120 participants (60 females and 60 males) ages 18 to 25 years to study the link of Humour Styles with Adult Attachment Styles and Conflict Management. Correlation and regression were used to analyse the data. The research findings indicate that Affiliative Humour Style and Self-Enhancing Humour Style had a positive relationship with closed attachment style, understanding natural response, understanding context, and apply approach. Aggressive Humour Style has a positive relationship with anxiety attachment style and a negative relationship with understanding natural responses, understanding context, and apply approach. Self-Defeating Humour Style has a negative relationship with depend attachment style.
Keywords: Humour Styles; Affiliative Humour; Self-Enhancing Humour; Aggressive Humour; Self-Defeating Humour; Attachment Style; Closed Attachment; Depend Attachment; Anxiety Attachment; Conflict Management